The dual system model of distraction: explaining the cognitive mechanism of distraction - Wang, Chenghao (Frontiers in Psychology, 2025)
In this conceptual analysis, the theoretical foundations of distraction are examined, with particular emphasis on its definitional ambiguity and the absence of systematic models. The dual system model of distraction is introduced, delineating two complementary mechanisms: the distraction capacity system, a limited unconscious mechanism that automatically resists task-irrelevant input, and the attention control system, a conscious mechanism that reorients focus when distraction exceeds capacity. The first aim is to situate distraction in relation to established attention theories, showing how filter, attenuation, and capacity models frame distraction only indirectly. A review of contemporary distraction-related accounts and findings, such as goal interference and resource availability models, is then provided to demonstrate the lack of a unified framework. On this basis, the dual system model is explained as accounting for inattentional blindness, inattentional deafness, the state of flow, and the transition from recognizing distraction to re-engaging with the primary task. The model’s relevance for educational contexts is outlined, where technology-induced distractions present a pressing challenge for sustained attention. Finally, it is argued that the dual system model serves as an epistemic framework that integrates unconscious resistance and conscious control, thereby providing a conceptual foundation for future empirical research and applied interventions in distraction-prone environments.